Pamphilius ishikawai feeds on Astilbe: the first record of Pamphiliidae (Hymenoptera) associated with Saxifragaceae - Shinohara, Akihiko; Kameda, Yuichi; Ibuki, Shin-Ichi; Kiyoshi, Takuya; Kakuda, Tsuneo; Kojima, Haruyoshi (Zootaxa, 2016)
Based on field observations and rearing experiments in Nagano and Tochigi prefectures in central Honshu, Japan, host plants and life history of a leaf-rolling sawfly, Pamphilius ishikawai Shinohara, 1979, are recorded for the first time. The larva is a solitary leaf-roller on Astilbe. This is the first record of the Saxifragaceae as a host plant of the Pamphiliidae. We made molecular phylogenetic analysis using mitochondrial cytochrome oxidase subunit 1 (COI) gene sequences for nine individuals of P. ishikawai feeding on three different species of Astilbe in two localities with different climates and for six outgroup pamphiliine species. It revealed very small genetic variability within P. ishikawai and suggested probable monophyly of the P. sulphureipes group.